The Ship of the Dead - Riordan, Rick (Riordan, Rick. Magnus Chase and the gods of Asgard., 2017)
While Loki prepares his ship, Naglfar, to begin the final battle of Ragnarok, Magnus and his friends set sail to reach the vessel before it's ready, but angry sea gods and a fire-breathing dragon may prevent them from arriving in time.